Від редактора: Політика - це не видовищний спорт: щодо ролі психолінгвістів у добу глобальної кризи - Hartshorne, Joshua (Східноєвропейський журнал психолінгвістики, 2022)
As psycholinguists, much of our time is spent steeped in abstraction, considering the nature of the mind. Every once in a while, we might raise our heads from our desks, gaze around, and wonder at the world around us and whether anyone might improve its state. Then it is back to binding principles, implicatures, and phonotactics. I believe in basic science, that knowledge is a per se good, and that more knowledge is more better. But I also believe that these goods will only accrue if there is a functioning society for them to accrue in – the prospect of which, as the threats of climate change, nuclear war, and genocide so frequently remind us, is by no means certain. Finally, I believe that my colleagues are possessed of a striking wealth of knowledge and ability that must, to be blunt, be good for something. Or perhaps not. Perhaps, in the face of societal threats, our skills are entirely extraneous, and our time is best spent knocking doors, calling representatives (if we are so fortunate as to have representatives), feeding refugees, comforting the afflicted, trading in our cars for bicycles, or heading to the battlefield. That is, I take it as a given that we should – all of us – be actively participating in constructing the world we wish to live in. Politics is not a mere spectator sport, in which we root and cheer and wear our favorite players’ jerseys. Society is what its members make it, and sitting on the sidelines affects the outcome just as much as getting out on the field. The question, then, is whether we should be contributing as psycholinguists. Hence this special issue. The goal was certainly not to win the war through psycholinguistics. We are still (mostly) basic scientists, and even research on application unfolds too slowly to be of immediate use for the present conflict. The question, then, is whether we have anything to contribute to mitigating the consequences of the war, speeding recovery, preparing for or preempting the next one, and generally contributing to building the world we wish to live in. That question is too broad to be answered definitively with a single special issue, particularly one compiled under less-than-ideal conditions. (Many of the authors are refugees. In some cases, final revisions had to be completed on only a couple hours of electricity per day.) Call it a pilot project. The contributors illustrate a number of ways psycholinguists might contribute. One set of contributions considers the role of language and communication in both fomenting and responding to conflict. Isacoff provides a theoretical overview of linguistic tools for promoting sectarian violence. Krylova-Grek provides a theoretically-motivated descriptive analysis of hate speech in Russian media. Matsuoka & Matsuoka provide a detailed, line-by-line exegesis of the rhetorical strategies employed by Volodymyr Zelensky in his speech to the Japanese parliament, with a particular focus on mechanisms of building empathy and solidarity. Taking this a step further, both Ushchyna and Kovalchuk & Litkovych document in real time the emergence of new words and other linguistic devices that are allowing Ukrainians to quickly convey to one another their shared experiences and values. (American audiences may find easy analogies to the emergence of societal buzzwords like “alternative facts” or “deplorables” or “red-pilled” – phrases that quickly expanded beyond their original usage to indirectly denote a cultural affiliation.) Another set of contributions focuses on the linguistic consequences of conflict. Yeter, Rabagliati, & Özge draw on a broad literature to consider how the refugee experience interrupts children’s linguistic & cognitive development. Labenko & Skrypnyk complement this with a detailed linguistic analysis of sixty child refugees from the Russian invasion of Ukraine. Chrabaszcz and colleagues present a more strictly applied study, addressing an even more direct consequence of displacement: many refugees land in countries where they do not know the language. The authors report on two crowd-sourced projects to provide virtual language instruction to refugees. A possible application for many of these lines of work is to monitor and track societal mood in real time. Karpina & Chen use computational methods to analyze Ukraine-related statements on Twitter by four prominent Western politicians during the early course of the war. Zasiekin, Kuperman, Hlova, & Zasiekina apply similar methods to analyzing mental state from Ukrainian war narratives posted on social media. The scope of both projects is limited by time pressure, power outages, and the like, but they join a larger literature in which researchers are increasingly using computational analysis of speech for applications ranging from monitoring hate speech to neuroclinical assessment (Lehr et al., 2012; Liu et al., 2022; Schmidt & Wiegand, 2017). As of writing, the war in Ukraine continues. Psycholinguistics will not end it. I leave it to the readers of this issue to determine, after having considered the contributions herein, whether psycholinguists qua psycholinguists have a role to play in the broader societal context, and what, if any, your own role should be.